Porous Properties of Pillared Carbons Prepared from the Thermal Reduction of Graphite Oxide Repeatedly Silylated with Methyltrichlorosilanes - Matsuo, Yoshiaki; Hayashida, Akihiro; Konishi, Kentaro (Frontiers in Materials, 2015)
Pillared carbons with interlayer spacings of 1.27–1.37 nm were obtained from graphite oxide repeatedly silylated with methyltrichlorosilane, when the content of it was higher than 1.5/GO unit. The BET surface area of the resulting pillared carbons reached 723 m2/g and decreased with the increase in the content of Si because of the increase in the density of pillar. Based on the intercalation behaviors of n-alkylamine molecules into pillared carbons, it has been concluded that the entrance for organic molecules between pillars and length of pillars were almost independent of the pillar density. The molecular length of n-butylamine molecule added during the silylation of graphite oxide seems to determine the length of the pillars.